2008
DOI: 10.1124/mol.108.046201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IκB Kinase-Nuclear Factor-κB Signaling Pathway by 3,5-Bis(2-flurobenzylidene)piperidin-4-one (EF24), a Novel Monoketone Analog of Curcumin

Abstract: The nuclear factor-B (NF-B) signaling pathway has been targeted for therapeutic applications in a variety of human diseases, includuing cancer. Many naturally occurring substances, including curcumin, have been investigated for their actions on the NF-B pathway because of their significant therapeutic potential and safety profile. A synthetic monoketone compound termed 3,5-bis(2-flurobenzylidene)piperidin-4-one (EF24) was developed from curcumin and exhibited potent anticancer activity. Here, we report a mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(163 citation statements)
references
References 31 publications
6
156
0
1
Order By: Relevance
“…Curcumin is able to suppress NF-κB activation by an Akt-dependent or Akt-independent inhibition of IKK (15,16,45). Certain curcumin analogues, including 3,5-bis(2-flurobenzylidene) piperidin-4-one (EF24) have been found to have a potent inhibitory effect on NF-κB (46). In the present study, we identified that 5 out of 6 cyclohexanone curcumin analogues tested had a more potent inhibitory effect than curcumin on activation of NF-κB in PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is able to suppress NF-κB activation by an Akt-dependent or Akt-independent inhibition of IKK (15,16,45). Certain curcumin analogues, including 3,5-bis(2-flurobenzylidene) piperidin-4-one (EF24) have been found to have a potent inhibitory effect on NF-κB (46). In the present study, we identified that 5 out of 6 cyclohexanone curcumin analogues tested had a more potent inhibitory effect than curcumin on activation of NF-κB in PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, curcumin has been shown to inhibit NF-jB activation in ovarian cancer cells [30,36]. In several ovarian cancer cell lines (SKOV3ip1 and HeyA8), curcumin suppressed NF-jB and STAT-3 activation and inhibited expression of COX-2 [36].…”
Section: Curcuminmentioning
confidence: 99%
“…However, treatment with 20 µM curcumin downregulated the constitutively active NF-κB in the REH cell line, both alone and in combination with all the therapeutic agents tested. It is postulated that this downregulation occurs via activation of the inhibitor of kappa B α (24).…”
Section: Discussionmentioning
confidence: 99%